Compact Antennas for High Data Rate Communication Ultra-wideband (UWB) and Multiple-Input-Multiple-Output (MIMO) Technology - Malik, Jagannath (Springer Topics in Signal Processing,, 2018)
This book discusses the development of promising technologies for compact antennas for high data-rate communications. It discusses and analyzes the design of compact ultra-wideband (UWB) and multiple input, multiple output (MIMO) antennas, providing essential know-how for designers, practicing engineers and scientists. These wireless communication technologies enable consumers to have convenient access to a wide range of services - anytime, anywhere. And the introduction of wireless mobile access points eliminates the limitations to communication imposed by geographical location. The Internet has allowed people to access and share information much more rapidly, but in order to achieve higher data rates with the limited available resources and imposed constraints, wireless communication technology needs to be pushed beyond the physical limits of the propagation channel. This book contributes to achieving this goal.